A mediação em projetos de incentivo à leitura: a apropriação da informação para construção do conhecimento e do pensamento crítico - Oliveira, Heloá Cristina Camargo de [UNESP] (2015)
It is understood that mediation proves important as the way to a more committed socially performance in reading incentive practices. It is through that it is created forms of action that have the significant approaches based, for example, guided by the appropriation of information and knowledge construction. In this sense, the reading is presented as an important factor, with the basic requirement for the appropriation of information. However, it is cleared that there is a certain lack of the studies directly focused to the topic within the Information Science. In this way, it is seeked to analyze the relationships between practices to encourage reading and mediation of information, in particular the aspects related to the interference of agents, information appropriation and the construction of knowledge and critical thinking. Therefore, it delimited as focus of analysis the practices developed in the city of Londrina, within the state of Paraná, specifically in the award-winning Project Bibliotecas Escolares: Palavras Andantes, developed by Londrina Department of Education since 2002. It was used a qualitative approach and exploratory method by mean of Discourse Analysis (AD) technique and the Discourse of the Collective Subject (DCS) to analyze the data obtained in interviews, documents and notices. It was found that the strengthening of the mediation process bases may be the key to that review must have more impacts outlined in projects such as what constitutes the universe for this work. At the end, It is proposed a restructuring of the bases of reading incentive projects for the optimization of these, in order to widely promote the appropriation of information, and the construction of knowledge and critical thinking.